Pengaruh Budaya Sekolah, Servant Leadership dan Kedisiplinan Guru dalam Implementasi Platform Merdeka Mengajar pada Guru Penggerak Sekolah Dasar di Kabupaten Aceh Barat - Saiful, Bahri; Husaini, Husaini; Tawakal, Tawakal; Afriana, Afriana (peusangan, 2024)
This research aims to analyze the influence of school culture, servant leadership and teacher discipline in the implementation of the independent teaching platform. The object of the research was a sample of 72 elementary school teachers in West Aceh Regency. Using quantitative research with an infrential statistical approach, namely path analysis. The research results show several findings, namely: a). There is a direct and indirect influence of school culture on the implementation of the independent teaching platform, namely 21.68%. b). There is a direct and indirect influence of servant leadership on the implementation of the independent teaching platform of 30.36%. c). There is a direct and indirect influence of teacher discipline on the implementation of the independent teaching platform of 14.57%. And d). The contribution of school culture factors, servant leadership and teacher discipline to the implementation of the independent teaching platform for teachers driving SDN West Aceh Regency was 66.7%.